Upward trends of syphilis in the non-pregnant adults: A six-year report on clinical and epidemiological profile of syphilis from a tertiary care center, India - Solaimalai, Dhanalakshmi; Gupta, Ankan; George, Leni; Manesh, Abi; Karthik, Rajiv; Sathishkumar, Dharshini; Peter, C. V Dincy; Varghese, George M; Pulimood, Susanne A; Kannangai, Rajesh; Prakash, John AJ (Frontiers in Public Health, 2022)
Since 2000, a resurgence of syphilis has been noted in many developed and developing countries, especially among men who have sex with men (MSM). Incidence and prevalence of syphilis in pregnant women have been reduced drastically by mandatory screening in early pregnancy. Insufficient data in other populations especially from developing countries limit targeted public health interventions. This study aimed to describe the clinical and epidemiological profile of serologically confirmed syphilis cases among the nonpregnant high-risk group reporting to a tertiary care centre in Southern India. A retrospective study was carried out in a tertiary care centre in Southern India for six years from 2015 to 2020. A total of 265 serologically confirmed syphilis patients were included. A statistically significant increase in positivity from 0.52% to 2.1% was observed in this study (2015 to 2020). Among risk factors, high-risk behaviour with multiple heterosexual partners was the commonest (51.3%), followed by marital partners who tested positive (9.4%) and MSM (7.5%). The majority of the patients were diagnosed at the latent stage (79%), followed by secondary syphilis (10%) and tertiary syphilis (8%). A quarter of patients (23%) were coinfected with HIV. Serological non-responsiveness was more common among HIV infected (47% vs 24%). Sixteen had neurosyphilis and six had ocular involvement. HIV co-infection complicated 50% (8/16) of neurosyphilis patients. Syphilis is still prevalent, especially in high-risk groups including those are attending STI clinics. Further prospective multicentric studies are needed to identify and implement public health measures.